4(4x-1)=4(6x-1)

Simple and best practice solution for 4(4x-1)=4(6x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x-1)=4(6x-1) equation:


Simplifying
4(4x + -1) = 4(6x + -1)

Reorder the terms:
4(-1 + 4x) = 4(6x + -1)
(-1 * 4 + 4x * 4) = 4(6x + -1)
(-4 + 16x) = 4(6x + -1)

Reorder the terms:
-4 + 16x = 4(-1 + 6x)
-4 + 16x = (-1 * 4 + 6x * 4)
-4 + 16x = (-4 + 24x)

Add '4' to each side of the equation.
-4 + 4 + 16x = -4 + 4 + 24x

Combine like terms: -4 + 4 = 0
0 + 16x = -4 + 4 + 24x
16x = -4 + 4 + 24x

Combine like terms: -4 + 4 = 0
16x = 0 + 24x
16x = 24x

Solving
16x = 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
16x + -24x = 24x + -24x

Combine like terms: 16x + -24x = -8x
-8x = 24x + -24x

Combine like terms: 24x + -24x = 0
-8x = 0

Divide each side by '-8'.
x = 0

Simplifying
x = 0

See similar equations:

| 17k=-136 | | 4/18=15/c | | 9(2b+8)+11= | | (8y^6)^(-1/3) | | 0.069(-63.7)(x)+0.1(1.1)+0.059(0.22)(1.1)=0 | | -2.5x-4=35 | | 15n=165 | | 7=10e+7 | | (11/2)r+8=(5/2)r+20 | | 20-b=13 | | 9(2b+8)= | | 0.0695(-68.1)(x)+0.1(3.7)+0.059(0.22)(3.7)=0 | | y-20=-5 | | 4m=4 | | -42=-7k | | 3/c=27/9 | | 3(3f+5)=24 | | A+14=-3 | | 3-6y=0 | | f(n)=3f(n-1)+2 | | 288=18v | | n/2,400=5 | | 6m-3=3m+24 | | 0.071(-71.3)(x)+0.1(4.3)+0.059(0.22)(4.3)=0 | | B-(-2)=19 | | 5+2timesg=20 | | q-2=2 | | 40a^4-5a= | | 7y-1f=17 | | 4(y-7)=3(6+2y) | | -41=4-9r | | -x=-7x+16 |

Equations solver categories